DISENGAGEMENT; STRATEGI PENANGGULANGAN TERORISME DI INDONESIA - Fakhri Usmita (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
This article aims to review the opinion of some figures about the opportunities and barriers to implementation of disengagement as a counter-terrorism strategy in Indonesia. This approach is a response to the impasse de-radicalization approach in dealing with members of the terrorist group based on religious ideology. By using qualitative methods we can see that most of the sources found disengagement strategy can be applied in the fight against terrorism in Indonesia. Implementation of disengagement is possible because the majority of religious adherents in Indonesia is among the moderate, strong family ties, the possibility of disagreement among terrorist groups in Indonesia, and the humanist approach that made the Police can be the way of success of this strategy. Although there are barrier, but this problem can be overcome if there is good faith of all elements of society and make terrorism as a common enemy.